Surgical Reconstructive Therapy of Peri‐Implantitis via Submerged Versus Non‐Submerged Healing: A 2‐Year Retrospective Study - Sila Cagri Isler; Kaan Tekbudak; Fatma Soysal; Zeynep Aksu; Özlem Kaymaz; Secil Karakoca Nemli; Andrea Roccuzzo; Berrin Unsal (Clinical Implant Dentistry and Related Research, 2026)
ABSTRACT Introduction To compare the clinical, radiographic, and patient‐reported outcomes of submerged and non‐submerged healing modalities in the reconstructive surgical treatment of peri‐implantitis, and to evaluate factors associated with treatment success. Materials and Methods Patient records from individuals treated for peri‐implantitis with reconstructive surgical therapy were retrospectively analyzed. Implants were treated using either a non‐submerged or submerged approach, with biomaterial application consisting of grafting alone or grafting combined with a collagen membrane. Clinical, radiographic, and patient‐reported outcome measures (PROMs) were assessed. Treatment success was defined as absence of suppuration (SOP), absence of bleeding on probing (BOP) or bleeding at no more than one site, reduction in probing depth (PD), no additional marginal bone loss, and mucosal recession (MR) change of ≤ 1 mm. A cost‐effectiveness analysis was additionally performed based on treatment success across predefined cost categories reflecting combinations of healing modality and biomaterial use. Data were analyzed using linear and generalized mixed models, and a generalized estimating equation model was applied for treatment success analysis. Results A total of 33 patients (53 implants) met the eligibility criteria and were included in the analysis. No significant differences in treatment success were observed between healing modalities ( p > 0.05), although the submerged approach showed a tendency toward higher success rates across follow‐up periods, irrespective of biomaterial use. Significant improvements over time were observed for clinical parameters, including plaque index (PI), BOP, PD, and SOP ( p < 0.001). A significant group × time interaction was identified for PI, keratinized tissue height, and marginal bone level change ( p < 0.05). PROMs revealed lower pain/discomfort and higher esthetic and satisfaction scores in the submerged group. Multivariate analysis identified history of periodontitis and baseline deepest PD as significant predictors of treatment success at 2 years postoperatively ( p < 0.05). Conclusion Over a 2‐year follow‐up, treatment success rates were comparable between submerged and non‐submerged healing modalities following reconstructive surgical treatment of peri‐implantitis, while submerged healing was associated with significantly better esthetic outcomes and higher patient satisfaction. History of periodontitis and greater baseline deepest PD were associated with less favorable treatment outcomes.